Autoantibodies Targeting Intracellular and Extracellular Proteins in Autoimmunity - Burbelo, Peter D.; Iadarola, Michael J.; Keller, Jason M.; Warner, Blake M. (Frontiers in Immunology, 2021)
Detecting autoantibodies provides foundational information for the diagnosis of most autoimmune diseases. An important pathophysiological distinction is whether autoantibodies are directed against extracellular or intracellular proteins. Autoantibodies targeting extracellular domains of proteins, such as membrane receptors, channels or secreted molecules are often directly pathogenic, whereby autoantibody binding to the autoantigen disrupts the normal function of a critical protein or pathway, and/or triggers antibody-dependent cell surface complement killing. By comparison, autoantibodies directed against intracellular proteins are recognized as useful diagnostic biomarkers of abnormal autoimmune activity, but the link between antigenicity and pathogenicity is less straightforward. Because intracellular autoantigens are generally inaccessible to autoantibody binding, for the most part, they do not directly contribute to pathogenesis. In a few diseases, autoantibodies to intracellular targets cause damage indirectly by immune complex formation, immune activation and other processes. In this review, the general features of and differences between autoimmune diseases segregated on the basis of intracellular or extracellular autoantigens are explored using over twenty examples. Expression profiles of autoantigens in relation to the tissues targeted by autoimmune disease and the temporal appearance of autoantibodies before clinical diagnosis often correlate with whether the respective autoantibodies mostly recognize either intracellular or extracellular autoantigens. In addition, current therapeutic strategies are discussed from this vantage point. One drug, rituximab, depletes CD20+ B-cells and is highly effective for autoimmune disorders associated with autoantibodies against extracellular autoantigens. In contrast, diseases associated with autoantibodies directed predominately against intracellular autoantigens show much more complex immune cell involvement, such as T-cell mediated tissue damage, and require different strategies for optimal therapeutic benefit. Understanding the clinical ramifications of autoimmunity derived from by autoantibodies against either intracellular or extracellular autoantigens, or a spectrum of both, has practical implications for guiding drug development, generating monitoring tools, stratification of patient interventions, and designing trials based on predictive autoantibody profiles for autoimmune diseases.